PEMANFAATAN PELAYANAN JAMINAN PERSALINAN (JAMPERSAL) OLEH IBU BERSALIN DI PUSKESMAS X TAHUN 2013 - Renny Listiawaty (GoAcademica Research dan Publishing, 2020)
One of the government's policy to reduce the maternal mortality rate (MMR) is to launch Jampersal Program. This study purpose to describe the factors associated with utilization Maternity Insurance service (Jampersal) by maternal in Public Health Center X, Muaro Jambi Regency in 2013. The research method used a cross sectional sampling technique with proportional random sampling, after that followed by a qualitative approach through in-depth interviews and document review 9 informants. Quantitative research results showed that 31.1% Jampersal utilize. There is a significant relationship between the variables of age, education, knowledge, attitudes, beliefs, income, accessibility, the role of health workers and the need to use Jampersal. The most dominant variable is income after controlled by education, knowledge, income and accessibility. This study recommended midwives to give more intensive information, clear and complete to the community and always working to improve the quality of service Jampersal.